Studi Literatur: Media Digital untuk Meningkatkan Literasi Membaca Siswa Sekolah Dasar - Hardhika Wahyu Dewani (IJPSE Indonesian Journal of Primary Science Education, 2026)
One of the 21st-century skills that elementary school students must have is reading literacy. However, reading literacy in Indonesia is still low. The digital era brings significant changes in the learning process in elementary schools, including how students access, process, and understand texts. Digital media is increasingly used in students' reading activities. This study aims to determine digital learning media that can be used to improve reading literacy. This study uses a qualitative approach with a literature review. This literature review is based on research findings from the last 4 years found in Google Scholar. The results show that there are 10 digital learning media that are effective in improving elementary school students' reading literacy, namely Wordwall, digital-based interactive media, digital reading journals, digital learning media assisted by Quiziz, E-comics, Literacy Cloud, Let's Read platform, learning videos, Flipbook, and Canva-based interactive multimedia.